Analisis Kemungkinan Kebangrutan Berbasis Pendekatan Model Z-Score Altman dan Metode EVA pada PT X di Provinsi Kepulauan Bangka Belitung - melia catherin; budi purwanto (IPB University, 2016)
PT X has a regional office in Bangka Belitung Island Province which has been decrease in sales, increase in credit and inventory which may lead to insolvency. The purposes of this research was (1) to analyze the financial performance of PT X to learn factors affecting insolvency possibilities; (2) to analyze company condition that indicate insolvency possibilities; (3) to analyze the added values which could be given by the company in an insolvency possibility; (4) to analyze the relation of added values that had been given by the company with insolvent condition possibility. The primary data were gathered by interview. Secondary data consisted of financial reports, journal literatures, thesis, and related books. The data were processed through descriptive analysis, financial ratio, Z-score Altman model, and EVA method. Based on the descriptive analysis result, PT X was suffering a possibility of bankruptcy that may affect firm value which was also decrease. The financial ratio showed that cash ratio, operational profit margin, inventory cycle, credit cycle ratio, assets cycle ratio were decrease, DER and DAR were decreasing from 2010 until 2012, but it roused significantly in 2013 and turned back to decrease significantly on 2014. The result form Z-Score model showed that the company was in gray area in 2011, the company condition went better in 2012, but it went back to gray area in 2013-2014. The EVA result showed that PT X produced positive and decreased in EVA value from 2010 until 2014.